Lymphocyte subset abnormalities in early severe scleroderma favor a Th2 phenotype and are not altered by prior immunosuppressive therapy. (2nd February 2022) - Shah, Ankoor; Storek, Jan; Woolson, Rob; Pinckney, Ashley; Keyes-Elstein, Lynnette; Wallace, Paul K; Sempowski, Gregory D; McSweeney, Peter; Mayes, Maureen D; Crofford, Leslie; Csuka, M E; Phillips, Kristine; et al.
Abstract: Objectives: The Scleroderma: Cyclophosphamide or Transplantation (SCOT) trial compared hematopoietic stem cell transplant to CYC treatment in patients with early SSc with progressive skin and lung or kidney involvement. Here we describe lymphocyte phenotype abnormalities at study entry and the relation to prior DMARD therapy. Methods: Lymphocyte subsets ( n  = 26) measured by flow cytometry were compared in 123 heathy controls and 71 SCOT participants, including those given ( n  = 57) or not given ( n  = 14) DMARDs within 12 months of randomization. Results: Compared with healthy controls, individuals with SSc showed significant reductions in central memory CD8 T cells, activated total and CD4 T cells, γ/δ T cells, memory B cells, myeloid and plasmacytoid dendritic cells and FOXP3 + CD25 + Treg cells and increases in naïve CD4 T cells, effector memory CD4 T cells and effector CD8 T cells. A greater bias towards a IL-4 + Th2/T cytotoxic 2 (Tc2) phenotype based on the Th2:Th1 CD4 ratio and Tc2:Tc1 CD8 T cells was also found. Notably, no difference in any lymphocyte subset was observed between those given or not given prior DMARDs. Conclusions: In patients with early, severe SSc, significant lymphocyte subset abnormalities were observed. Prior treatment with immunosuppressive therapy did not impact the immunophenotype, suggesting that lymphocyte disturbances in scleroderma appeared to be due to the disease itself. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov ), NCT00114530.